HIJAB, PUNK, AND THE USE OF NEW TECHNOLOGIES IN COMMUNICATION - Rizky Hafiz Chaniago; Mohd Sufiean Hassan; Haddi Junaidi Kussin; Daniel Handoko (Perspektif Komunikasi Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2025)
To date, the role of women in the world of subcultures, especially Punk, is still considered small, especially in eastern countries where the majority of the population is Muslim, such as Indonesia. The influence of the mainstream media on negative images seems to cover up the small voices of women who are in the Punk subculture environment so that the general public does not know about their involvement in the arena. The negative image is getting stronger when women wearing hijab participate in this culture. Another reason that might be related to this rejection is that the image of a woman wearing a hijab with an elegant and respectable class is very different from the image of the Punk subculture, which is full of nuances of resistance/rebellion. As time goes by, with the development of the world, which is changing rapidly due to the influence of technology, the cultural space of subcultures also participates in the flow of globalization organically. The rapid advancement of new media such as social media opens up opportunities for women wearing hijab to be involved in the Punk subculture and more actively voice their ideology and talents. The main aim of the study is to analyze how women who wear the hijab communicate their voices through new technology. This study uses qualitative research with ethnographic methods. With the advent of new media, women wearing the hijab can freely present information related to the image of women in order to counteract the negative image of the Punk subculture in the eyes of the public.